The legendary Tun M / Mohd Hairie Mohd Nashoha - Mohd Nashoha, Mohd Hairie (Faculty of Art and Design, 2021)
Tun Mahathir bin Mohamad is the fourth and seventh former Prime Minister of Malaysia, a leading statesman of our country. His services and aspirations have greatly changed the modern environment of Malaysia and the perception of the outside community towards us. His boundless thinking and unexpected creative ideas were so admired that he was called the Father of Malaysian Modernization (Bapa Pemodenan Malaysia). Admiring Tun Mahathir's prowess, I have produced an outstanding portrait of him, as a token of my gratitude and that of the Malaysian community for his services. Through this artwork, I have chosen his most popular and well -known pictures and poses. This is intended to give the viewers a first capture of my artwork. Unlike other portrait paintings, this portrait of Tun Mahathir was produced using a combination of hand skills and laser technology, as symbolic of Tun's support for human skills and technology in developing our beloved country, Malaysia.